Pengaruh Net Profit Margin DanReturn On Equity Tehadap Return Saham Pada Industri Property Dan Real Estate Di Bursa Efek Indonesia Periode 2012-2017 - Noni Indah Pratiwi (Universitas Batanghari Jambi, 2019)
This research aims to describe Net Profit Margin,Return On Equity andReturn Saham on Industri Property and Real Estate Listed on Bursa Efek Indonesian (BEI) Period 2012-2017. Next also to analyze the influence of Net Profit Margin and Return On EquityonReturn Saham on Industri Property and Real Estate Listed on Bursa Efek Indonesian (BEI) Period 2012-2017. This research uses descriptive method quatitative correlation research with the from that describes the relation of independent variables with dependent variables. The research on promotion sales of purchases decision which are characterized by thitung> ttabel (2,083 > 2,022), then Ho rejected and Ha accepted.